Extending contact screening within a 50-m radius of an index tuberculosis patient using Xpert MTB/RIF in urban Pakistan: Did it impact treatment outcomes?. (March 2021) - Ul Haq, Mahboob; Hinderaker, Sven G.; Fatima, Razia; Shewade, Hemant Deepak; Heldal, Einar; Latif, Abdullah; Kumar, Ajay M.V.
Highlights: Evaluation of extended contact screening tuberculosis patient outcomes. Patients did not have inferior treatment outcomes. Patients did not have more unfavorable outcomes than routine cases. First study of this type in Pakistan. Abstract: Background: Pakistan implemented initiatives to detect tuberculosis (TB) patients through extended contact screening (ECS); it improved case detection but treatment outcomes need assessment. Objectives: To compare treatment outcomes of pulmonary TB (PTB) patients detected by ECS with those detected by routine passive case finding (PCF). Methods: A cohort study using secondary program data conducted in Lahore, Faisalabad and Rawalpindi districts and Islamabad in 2013–15. We used log binomial regression models to assess if ECS was associated with unfavorable treatment outcomes (death, loss-to-follow-up, failure, not evaluated) after adjusting for potential confounders. Results: We included 79, 431 people with PTB; 4604 (5.8%) were detected by ECS with 4052 (88%) bacteriologically confirmed. In all PTB patients the proportion with unfavorable outcomes was not significantly different in ECS group (9.6%) compared to PCF (9.9%), however, among bacteriologically confirmed patients unfavorable outcomes were significantly lower in ECS (9.9%) than PCF group (11.6%, P = 0.001). ECS was associated with a lower risk of unfavorable outcomes (adjusted relative risk (aRR) 0.90; 95% CI 0.82–0.99) among 'all PTB' patients and bacteriologically confirmed PTB patients (aRR 0.91; 95% CI 0.82–1.00). Conclusion: In PTB patients detected by ECS the treatment outcomes were not inferior to those detected by PCF.